Development of Mackerel Odeng Substituted with Sword Bean Flour: Sensory Acceptability and Nutritional Composition - Raudatul Najwa Soraya Nurrizal; Rina Martini; Elzha Nur Fadila (Media Publikasi Cendekia Indonesia, 2026)
High snack consumption among adolescents demands balance with nutritious food products that are also appealing. Odeng, as Korean street food, has gained acceptance among adolescents. This study develops a product made from local food, mackerel odeng with sword bean flour substitution. The research used a Completely Randomized Design with three treatments: F1, F2, and F3. The organoleptic assessment of the products involved 30 semi-trained panelists to determine the level of preference and the characteristics of each formulation. Statistical analysis was done with SPSS 27.0, applying the Kruskal-Wallis test and the Mann-Whitney U test. The results of the hedonic organoleptic tests on the aspects of color, aroma, taste, and texture showed that F1 was the selected formula based on the Weighted Sum Method (WSM) with a substitution of 5 grams of sword bean flour. F1 contains 171 Cal/100 g; 17.95% protein; 6.75% fat; 9.62% carbohydrate; 0.2% omega 3; and 1.9% omega 6. The formula developed for this product has the potential to serve as a protein-rich snack and promote dietary diversification through the utilization of local food resources.